Developmental changes in the contributions of phonological processing skills to Chinese character reading and arithmetic. (April 2023) - Yang, Xiujie; Zheng, Mo; Liu, Kaichun
Abstract: This study examined the associations of phonological processing skills with reading and arithmetic ability in Chinese kindergartners (Mage = 5.56 years), third graders (Mage = 9.72 years), and fifth graders (Mage = 11.75 years) ( N  = 413) of Han descent. The results showed that phonological awareness and rapid automatized naming (RAN) showed stronger relations than phonological memory with reading and arithmetic across grades. Furthermore, the associations of phonological awareness and RAN with reading were much stronger in kindergartners than in primary school children, whereas their relationships with arithmetic remained stable across grades. Among phonological skills, phonological awareness has a unique influence on arithmetic that is independent of Chinese character reading in third-graders and kindergartners. In contrast, RAN uniquely explained the variation in arithmetic skills in fifth graders when reading was statistically controlled for. These findings have important implications for understanding the co-development of reading and arithmetic across grades and raise the possibility of training in phonological awareness and/or RAN to help children at risk for learning disabilities. Highlights: PA and RAN were more important than PM when correlating to Chinese reading and arithmetic. The relationship of PA with reading was stronger in kindergarten children than in primary school children. The association of RAN with reading was stronger in kindergarten children than in primary school children. PA has a unique influence on arithmetic independent of reading in third-graders and kindergartners. RAN uniquely explained the variation in arithmetic skills independent of reading in fifth-graders.